ANALISIS HUKUM ADMINISTRASI NEGARA TERHADAP PELAKSANAAN PEMEKARAN DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Jeffry Polie, Reynaldo (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2024)
This study aims to examine and analyze the relationship between State Administration Law and the Implementation of Regional Expansion. To know and analyze the Regional Expansion Implementation Mechanism according to Law Number 23 of 2014. The method used by researchers in this study is normative juridical. The results showed that there is a relationship between state administrative law and regional expansion policy and regional expansion procedures according to Law Number 23 of 2014 include several important stages. This includes collecting community aspirations related to expansion, regional expansion can be initiated by the central government, provincial government, relevant district/city government, or through local community proposals